A brief history of archaeology - Durrani, Nadia, author.
1 online resource
Keywords: "A Brief History of Archaeology details early digs as well as covering the development of archaeology as a multidisciplinary science, the modernization of meticulous excavation methods during the twentieth century, and the important discoveries that led to new ideas about the evolution of human societies. Spanning more than two thousand years of history, this short account of the discipline of archaeology tells of spectacular discoveries and the colorful lives of the archaeologists who made them, as well as of changing theories and current debates in the field. Early research at Stonehenge in Britain, burial mound excavations, and the exploration of Herculaneum and Pompeii culminate in the nineteenth-century debates over human antiquity and the theory of evolution. The book then moves on to the discovery of the world's pre-industrial civilizations in Egypt, Mesopotamia, and Central America, the excavations at Troy and Mycenae, the Royal Burials at Ur, Iraq, and the dramatic finding of the pharaoh Tutankhamun in 1922. The book concludes by considering recent sensational discoveries, and exploring the debates over processual and post processual theory which have intrigued archaeologists in the early twenty-first century. The third edition updates this respected introduction to one of the sciences' most fascinating disciplines. A Brief History of Archaeology is a vivid narrative that will engage readers who are new to the discipline, drawing on the authors' extensive experience in the field and classroom"--